2018
DOI: 10.1021/acs.jpclett.8b01919
|View full text |Cite
|
Sign up to set email alerts
|

Structural Tuning of Quantum Decoherence and Coherent Energy Transfer in Photosynthetic Light Harvesting

Abstract: Photosynthetic organisms capture energy from solar photons by constructing light-harvesting proteins containing arrays of electronic chromophores. Collective excitations (excitons) arise when energy transfer between chromophores is coherent, or wavelike, in character. Here we demonstrate experimentally that coherent energy transfer to the lowest-energy excitons is principally controlled in a light-harvesting protein by the temporal persistence of quantum coherence rather than by the strength of vibronic coupli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 62 publications
(136 reference statements)
0
13
1
Order By: Relevance
“…Microscopy is a powerful tool for humans to observe the microcosm, which helps us understand the origin, development, and death of life . With the reduction of scales in microscopic observation, many novel quantum phenomena have been revealed and discussed. For example, researchers have confirmed that the efficient use of solar energy by photosynthesis in green plants is closely related to quantum coherence in both ensemble and single light-harvesting complexes. , In these processes, the microenvironment plays an essential role in maintaining the system quantum correlations in a steady state, which contributes to long-lived quantum coherence in photosynthetic complexes at physiological temperature. , Some other physiological processes, including energy metabolisms (e.g., respiratory processes , ) and cell canceration, are also related to the quantum coherent features of the cells. Investigations of cell physiology and disease pathogenesis heavily rely on untangling the complexity of intracellular quantum coherent mechanisms and pathways.…”
mentioning
confidence: 99%
“…Microscopy is a powerful tool for humans to observe the microcosm, which helps us understand the origin, development, and death of life . With the reduction of scales in microscopic observation, many novel quantum phenomena have been revealed and discussed. For example, researchers have confirmed that the efficient use of solar energy by photosynthesis in green plants is closely related to quantum coherence in both ensemble and single light-harvesting complexes. , In these processes, the microenvironment plays an essential role in maintaining the system quantum correlations in a steady state, which contributes to long-lived quantum coherence in photosynthetic complexes at physiological temperature. , Some other physiological processes, including energy metabolisms (e.g., respiratory processes , ) and cell canceration, are also related to the quantum coherent features of the cells. Investigations of cell physiology and disease pathogenesis heavily rely on untangling the complexity of intracellular quantum coherent mechanisms and pathways.…”
mentioning
confidence: 99%
“…As described above, coupling of chromophores to their environment in a LHC is thought to play a vital role in facilitating fast energy transfer. In one study of energy transfer from carotenoid peridinin donor to acceptor chlorophylls from marine dinoflagellates [184], the energy gap between donor and acceptor was tuned to modify, and thereby investigate, the role of electronic and vibrational coupling. The data-rich technique of 2DES demonstrated that minor changes to the chlorophyll functional groups (e.g., the formyl group) led to faster decoherence and lowered energy transfer efficiency within the complex [184].…”
Section: Bio-inspired Synthetic Light Harvesting Systemsmentioning
confidence: 99%
“…In one study of energy transfer from carotenoid peridinin donor to acceptor chlorophylls from marine dinoflagellates [184], the energy gap between donor and acceptor was tuned to modify, and thereby investigate, the role of electronic and vibrational coupling. The data-rich technique of 2DES demonstrated that minor changes to the chlorophyll functional groups (e.g., the formyl group) led to faster decoherence and lowered energy transfer efficiency within the complex [184]. An easily modifiable scaffold, such as the tobacco mosaic virus capsid protein, offers a highly versatile base from which chromophores can be attached at precise locations using linkers of varying length and rigidities.…”
Section: Bio-inspired Synthetic Light Harvesting Systemsmentioning
confidence: 99%
“…In complex molecular systems, such energy transport mechanisms are driven by ultra-fast non-adiabatic transitions through conical intersections (CI) [4][5][6][7][8][9]. Investigation of the coherent preparation of the donor state from the initial ground state and the control of the subsequent dynamics using intense, ultra-short laser pulses are major issues for modifying the energy transport mechanisms [10][11][12]. In this context, we have recently studied a rather complex molecular system, namely polyphenylene ethynylene dendrimer, with a control objective aiming at the coherent preparation of two donor states involved in the dynamics, or their symmetric versus asymmetric superposition [13].…”
Section: Introductionmentioning
confidence: 99%